2016
DOI: 10.1042/bcj20160146
|View full text |Cite
|
Sign up to set email alerts
|

The different catalytic roles of the metal-binding ligands in human 4-hydroxyphenylpyruvate dioxygenase

Abstract: 4-Hydroxyphenylpyruvate dioxygenase (HPPD) is a non-haem iron(II)-dependent oxygenase that catalyses the conversion of 4-hydroxyphenylpyruvate (HPP) to homogentisate (HG). In the active site, a strictly conserved 2-His-1-Glu facial triad co-ordinates the iron ready for catalysis. Substitution of these residues resulted in about a 10-fold decrease in the metal binding affinity, as measured by isothermal titration calorimetry, and a large reduction in enzyme catalytic efficiencies. The present study revealed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 52 publications
(74 reference statements)
1
20
0
Order By: Relevance
“…Extensive crystallographic and spectroscopic studies have shown that the metal ion is sixfold coordinated with the 2-His-1-Glu facial triad (His226 and His308 and one Glu394) and three water molecules at the active site [10, 30, 39]. Similarly, in HPPD-HPPA complex, the α -ketoglutarate moiety of HPPA in a bidentate interaction results in an octahedral coordination geometry involving the facial triad (Figure 1(b)).…”
Section: Resultsmentioning
confidence: 99%
“…Extensive crystallographic and spectroscopic studies have shown that the metal ion is sixfold coordinated with the 2-His-1-Glu facial triad (His226 and His308 and one Glu394) and three water molecules at the active site [10, 30, 39]. Similarly, in HPPD-HPPA complex, the α -ketoglutarate moiety of HPPA in a bidentate interaction results in an octahedral coordination geometry involving the facial triad (Figure 1(b)).…”
Section: Resultsmentioning
confidence: 99%
“…HPD acts upstream of FAH in the tyrosine catabolism pathway and Hpd disruption ameliorates HT-I symptoms by preventing the toxic metabolite build-up that results from loss of FAH. Structural analyses of HPD reveal that the catalytic domain of the HPD enzyme is located at the C-terminus of the enzyme and encoded by exon 13 and 14 [ 57 ]. Thus, frameshift-inducing indels upstream of exon 13 should render the enzyme inactive.…”
Section: Discussionmentioning
confidence: 99%
“…Structural analyses of HPD reveal that the catalytic domain of HPD enzyme is located at the Cterminus of the enzyme and encoded by exon 13 and 14 (54). Thus, frameshift-inducing indels upstream of exon 13 should render the enzyme inactive.…”
Section: Pathway Reprogramingmentioning
confidence: 99%